Rupiah Exchange Rate, Inflation, and Interest Rates Against LQ45 Index Share Prices Listed on the IDX in Banking Companies: Kurs Rupiah, Inflasi, dan Tingkat Suku Bunga Terhadap Harga Saham Indeks LQ45 yang Terdaftar di BEI pada Perusahaan Perbankan - Mawanda, Maulita Dhea; Setiyono, Wisnu Panggah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to examine the effect of the Rupiah Exchange Rate, Inflation, Interest Rates on Stock Prices. The approach used in this research is a quantitative approach. The population in this study are 45 LQ45 indexed companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling method. The sample in this study was 60 samples obtained from 5 banking companies included in the LQ45 index during the 2019-2021 period. The data used in this study is secondary data taken from the Indonesia Stock Exchange. Analysis of the data used in this study is Eviews version 9 with the aim of testing the Rupiah Exchange (X1), Inflation (X2), and Interest Rates (X3) on Stock Prices (Y). The results of this study indicate that simultaneously there is a significant effect between the Rupiah Exchange Rate, Inflation, and Interest Rates on Stock Prices. While partially the Rupiah exchange rate has a significant negative effect on stock prices and interest rates have a significant positive effect on stock prices, while inflation has no significant effect on stock prices.